Kepuasan Hidup Mahasiswa jurusan Psikologi mengikuti Pelatihan Analisis Data menggunakan Sintaks dengan Aplikasi Mplus - Yonathan Natanael (STKIP Andi Matappa, 2021)
The use of syntax in education is more focused on information technology and statistics study. So, this study aims to determine data analysis training using the syntax of one statistical software that increase the life satisfaction of social science student (one of them is a student majoring in Psychology). The training activities that are held measure life satisfaction twice, at the beginning and end of the training. The participants of the training were 86 students majoring in Psychology with ages ranged from 18 to 22 years old. The life satisfaction measurement instrument used is the Satisfaction with Life Scale (SWLS), while the statistical software used for training is Mplus. The result of the analysis found that there were differences in student life satisfaction before and after the training. Learning data analysis using syntax has a fairly effective effect on increasing life satisfaction of students majoring in Psychology in online training, students gain new knowledge and feelings in learning.